Prevalence of idiopathic scoliosis in athletes: a systematic review and meta-analysis. Issue 3 (5th August 2022) - Mousavi, Leila; Seidi, Foad; Minoonejad, Hooman; Nikouei, Farshad
Abstract : Objective: This study aimed to determine the prevalence of idiopathic scoliosis (IS) in child, adolescent and adult athletes of all sports activity levels. Design: Systematic review with meta-analysis. Data sources: Electronic databases (PubMed, Scopus, ProQuest, Sage journals, ScienceDirect, Google Scholar and Springer) were systematically searched up from inception to 28 September 2021. Eligibility criteria for selecting studies: Observational investigations were included to evaluate the prevalence of IS in athletes (engaged in any type of individual and team sports). Congenital scoliosis, neuromuscular scoliosis, Scheuermann's kyphosis and de novo scoliosis were not included. The risk of bias was assessed using the tool developed by Hoy et al. Results: Twenty-two studies were included (N=57 470, range 15–46544, participants), thirteen studies were of high-quality. The estimated prevalence of IS in athletes was 27% (95% CI 20% to 35%, I 2 =98%), with a 95% prediction interval (1% to 69%). The prevalence of IS was significantly higher in female athletes (35%, 95% CI 27% to 34%, I 2 =98%). Ballet dancers showed a high IS prevalence (35%, 95% CI 24% to 47%, I 2 =98%). Recreational athletes showed a higher IS prevalence (33%, 95% CI 24% to 43%, I 2 =98%) than at competitive-level athletes (0.05%, 95% CI 0.03% to 0.08%, I 2 =98%), followed by elite (20%, 95% CI 13% to 27%, I 2 =98%). Conclusions: The prevalence of IS in athletes was similar or higher to that as seen in other studies of the general population. IS prevalence may have a U-shaped relationship relative to level of competition. Further studies are required to determine which sports have the highest IS prevalence.